2015
DOI: 10.1002/fsn3.226
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nano‐composite and Thyme oil (Tymus Vulgaris L) coating on fruit quality of sweet cherry (Takdaneh Cv) during storage period

Abstract: Sweet cherry is one of the most appreciated fruit by consumers since it is an early season fruit and has an excellent quality. In this study effect of active nano composite formed from chitosan (as a matrix material), nano cellulose fiber (1% concentration) and Thyme oils (Tymus Vulgaris L) at 1% concentration on fruits quality was investigated. Treated fruits were stored at 1°C for 5 weeks and changes of different qualities attributes including weight loss, total acidity, TSS, anthocyanin, total sugar and mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…Similar trends were noticed for fruits or vegetables stored at ambient temperature or in the refrigerator (Kevers et al, ). The increase in TSS could be due to water loss by dehydration (Valverde et al, ) and activity of hydrolytic enzymes (Nabifarkhani, Sharifani, Daraei Garmakhany, Ganji Moghadam, & Shakeri, ). Quality degradation could be caused by combination of biochemical and microbial activities during storage period.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar trends were noticed for fruits or vegetables stored at ambient temperature or in the refrigerator (Kevers et al, ). The increase in TSS could be due to water loss by dehydration (Valverde et al, ) and activity of hydrolytic enzymes (Nabifarkhani, Sharifani, Daraei Garmakhany, Ganji Moghadam, & Shakeri, ). Quality degradation could be caused by combination of biochemical and microbial activities during storage period.…”
Section: Resultsmentioning
confidence: 99%
“…Curcumin concentration was 1.60 × 10 −3 M. Control: The sample was kept inside the treatment chamber at the same time intervals (0-20 min) as the treated samples but was not exposed to light emitting diode illumination. ND † = not detected in TSS could be due to water loss by dehydration (Valverde et al, 2005) and activity of hydrolytic enzymes (Nabifarkhani, Sharifani, Daraei Garmakhany, Ganji Moghadam, & Shakeri, 2015 (Valverde et al, 2005). The addition of these compounds lowered dehydration process.…”
Section: Effects Of Inactivation Of E Coli On Grapes Towards Physimentioning
confidence: 99%
“…Aurum and Nguyen (2019) reported an increase in TSS in grapes treated with curcumin-based photosensitization at a light dose of 36.3 J/cm 2 up to 4 days of storage at 37°C. This increase could be caused by dehydration (Valverde et al 2005) and activity of hydrolytic enzymes (Nabifarkhani et al 2015). Moreover, Baka et al (1999) found that strawberries treated with UV-C (doses 0.25 and 1.0 kJ/m 2 ) and stored at 4°C increased free sugar content up to 6 days.…”
Section: Sugar Contentmentioning
confidence: 98%
“…Increased total sugar content might be due to conversion of starch into sugars (Tsuda et al, 1999). Also, Vesaltalab and Gholami (2012) and Nabifarkhani et al (2015), they suggested that total sugar content increased during storage period that may be due to the dehydration and decomposition of organic acids (used as an energy source) in the fruits.…”
Section: Sugar Fractionsmentioning
confidence: 98%